Equianalgesic potency ratios of opioids used in patient-controlled analgesia: A network meta-analysis - Dinges, MD, Hanns-Christian; Schubert, MD, Ann-Kristin; Rücker, PhD, Gerta; Otto, MD, Stephan; Waldmann, Dipl Ing Agr, Susanne; Wiesmann, MD, Thomas; Wulf, MD, Hinnerk; Eberhart, MD, MA, Leopold; Gehling, MD, Markus (Journal of Opioid Management, 2022)
Objective: To determine equianalgesic potency ratios for opioids with an evidence-based approach without the use of pre-existing potency tables. Design: Frequentist network meta-analysis (NMA) of randomized controlled trials (RCTs) comparing opioids in patient-controlled analgesia (PCA). Setting: A systematic review. Data sources: A systematic search of MEDLINE, EMBASE, the Cochrane Library (CENTRAL), and Web of Science identified relevant RCTs from start of recording to 2019. Eligibility criteria: RCTs comparing opioids via intravenous PCA in acute pain, with comparable resulting pain scores and identical treatment with coanalgesics at study level. The quality of studies was assessed using the Cochrane risk of bias tool with six items. Results: 52 RCTs were identified with data for 16 opioids. Primary endpoint was the inverted ratio of means of the total consumption administered via PCA, which resembles the analgesic potency. The calculated analgesic potencies were sufentanil 423 [95 percent CI 334.99; 532.96], fentanyl 58 [48.22; 68.60], buprenorphine 37 [26.66; 50.81], remifentanil 13 [9.37; 19.13], alfentanil 7 [4.02; 11.01], hydromorphone 6 [4.96; 8.43], oxymorphone 6 [4.46; 8.84], butorphanol 4.5 [3.05; 6.73], diamorphine 2.2 [1.16; 4.10], morphine 1, oxycodone 0.9 [0.65; 1.34], piritramide 0.9 [0.55; 1.56], nalbuphine 0.7 [0.54; 0.95], pethidine 0.12 [0.10; 0.15], meptazinol 0.08 [0.03; 0.20], and tramadol 0.08 [0.07; 0.10]. Conclusions: The results in part contradict the values from the literature, which have been criticized for their imprecision. From clinical experience however, our findings seem very plausible. Short-acting opioids are less potent compared to longer acting drugs, eg, morphine, probably due to shorter intervals for readministration.